Jerzy Harasymowicz - poeta pogranicza - Ksenicz, Andrzej (Acta Polono-Ruthenica, 2018)
The article tries to show Harasymowicz as a poet working under the influence of two cultures. In his poetry relations of Polish and Ukrainian cultures are shown on the cultural and historical background, which are even evident in his first volume of poetry which was published in 1956. The geographical area of the Carpathian mountains and Low Beskids hold a special place in his poetry. Family tradition, objectivity of the poet and his delight in mountain scenery for „the dream and a fairy-tale world” created a metaphorical image of the area and people living in it.